Ruqyah Syar’i: Signifikansi Dan Pengaruh Surat Al-Fatihah Dalam Praktik Ruqyah - Agus Rifki Ridwan; Ris’an Rusli; Halimatuss’adiyah Halimatuss’adiyah (Jurnal Semiotika Quran, 2023)
Basically the study of the Qur'an does not necessarily focus on the text of the Qur'an. However, it can also refer to social phenomena associated with the presence of the Qur'an in certain Muslim communities, as well as other individuals who are involved with it on a daily basis or what is often referred to as the Living Qur'an. The Qur'an lives in society and is known as the Living Qur'an. In contrast to most Al-Qur'an studies which concentrate on the text of the Al-Qur'an, this article aims to bring the evolution of Al-Qur'an studies into the realm of the Living Qur'an. An interesting option in its development may be the living Koran. The research findings show that Surah Al-Fatihah can be used to perform meruqyah for individuals.